STUDENTS’ PERCEPTION TOWARD USING DUOLINGO FOR LEARNING ENGLISH - Hawa, Zaharah Linal; Roslaini, Roslaini (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2024)
This study investigates students' perceptions of Duolingo as an English language learning aid. It focuses on usefulness, motivation, and effectiveness in improving language skills. As digital language learning platforms grow in popularity, understanding user experience and satisfaction is important to assess their impact on language acquisition. The study uses a quantitative open-ended survey consisting of 16 questions. Data was collected using Google Forms and analyzed using a 5-Likert scale. Data was analyzed using SPSS. In terms of language skill development, students reported significant gains in the areas of grammar, vocabulary, reading, listening, and writing. Duolingo's diverse exercises and activities are proven to improve practical language skills and provide a comprehensive, engaging learning experience. Responses to collect data from a sample of students using Duolingo to learn English. The survey indicates positive perceptions of Duolingo among students, highlighting its potential as a valuable resource for English language learners. By continually developing and incorporating user feedback, Duolingo can further strengthen its role in language education, providing learners with an effective and enjoyable path to English proficiency.